The anticonvulsant phytocannabinoids CBGVA and CBDVA inhibit recombinant T-type channels - Udoh, Michael; Bladen, Chris; Heblinski, Marika; Luo, Jia Lin; Janve, Vaishali S.; Anderson, Lyndsey L.; McGregor, Iain S.; Arnold, Jonathon C. (Frontiers in Pharmacology, 2022)
Introduction: Cannabidiol (CBD) has been clinically approved for intractable epilepsies, offering hope that novel anticonvulsants in the phytocannabinoid class might be developed. Looking beyond CBD, we have recently reported that a series of biosynthetic precursor molecules found in cannabis display anticonvulsant properties. However, information on the pharmacological activities of these compounds on CNS drug targets is limited. The current study aimed to fill this knowledge gap by investigating whether anticonvulsant phytocannabinoids affect T-type calcium channels, which are known to modulate neuronal excitability, and may be relevant to the anti-seizure effects of this class of compounds. Materials and Methods: A fluorescence-based assay was used to screen the ability of the phytocannabinoids to inhibit human T-type calcium channels overexpressed in HEK-293 cells. The most potent compounds were further examined using patch-clamp electrophysiology. Alphascreen technology was used to characterise selected compounds against G-protein coupled-receptor 55 (GPR55) overexpressed in HEK-293 cells, as GPR55 is another target of the phytocannabinoids. Results: A single concentration screen in the fluorescence-based assay showed the phytocannabinoids inhibited T-type channels with substantial effects on Cav3.1 and Cav3.2 channels compared to the Cav3.3 channel. The anticonvulsant phytocannabinoids cannabigerovarinic acid (CBGVA) and cannabidivarinic acid (CBDVA) had the most significant effects, so were fully characterized in concentration-response studies. CBGVA and CBDVA had IC50 values of 6 µM and 2 µM on Cav3.1 channels; 2 µM and 11 µM on Cav3.2 channels, respectively. Biophysical studies at Cav3.1 showed that CBGVA caused a hyperpolarisation shift of steady-state inhibition. Both CBGVA and CBDVA had a use-dependent effect and preferentially inhibited Cav3.1 current in a slow inactivated state. CBGVA and CBDVA were also shown to antagonise GPR55. Conclusions and implications: These findings show that CBGVA and CBDVA inhibit T-type calcium channels and GPR55. These compounds should be further investigated to develop novel therapeutics for treating diseases associated with dysfunctional T-type channel activity.